PERHITUNGAN PRODUKTIFITAS ALAT BERAT PADA PEKERJAAN NORMALISASI SUNGAI LOA-ALA KM 1 KECAMATAN LOA JANAN KUKAR - KARNAIN, ZUL (KURVA S JURNAL MAHASISWA, 2013)
ABSTRACT In the "Calculation of Equipment Productivity At Work Normalization Loa-Ala River Km 1 Loa Janan aquatic mammal". Is an implementation of the sector to advance the field  of  irrigation.  It  is  therefore  required  the  use  of  heavy  equipment,  so  that  job execution can be achieved according to predetermined targets and the use of heavy equipment must be well planned and carefully, so that its precise, optimal production and efficient in terms of the equipment baiaya excavation and embankment on the River jobs Normalization.  The  results  of  calculations  using  the  job  execution  time  of  heavy equipment for excavation work, and piles are:  Excavation work using type Exavator Komatsu PC 200 (1 unit), then a period of 27 days was obtained.   pekrjaan Land transport job by using the Dump Truck type Mitsubishi 135 PS (3 units), then the time obtained is 20 days.  Work of the spreading / barrow using Komatsu Bulldozer type D 85E (1 unit), then the time obtained is 10 days.  Soil compaction jobs using type Compactor Bomag BW 212 D CAT (1 unit), then the time gained is 6 days